Truth and the past - Dummett, Michael A. E. (Columbia themes in philosophy., 2004)
Michael Dummett's three John Dewey Lectures?""The Concept of Truth, "" ""Statements About the Past, "" and ""The Metaphysics of Time""?were delivered at Columbia University in the spring of 2002. Revised and expanded, the lectures are presented here along with two new essays by Dummett, ""Truth: Deniers and Defenders"" and ""The Indispensability of the Concept of Truth.""In Truth and the Past, Dummett clarifies his current positions on the metaphysical issue of realism and the philosophy of language. He is best known as a proponent of antirealism, which loosely characterizes truth a.